Testes de germinação e vigor em sementes de feijão irrigado cultivar BRS Pérola - MARCONDES, Bruno Ruan Rossatti; LOPES, Adriano da Silva; FRANCO, Jhonatan da Silva; Marcos Jefferson (ANAIS DO ENIC, 2024)
-